Cavitation‐resistant junipers cease transpiration earlier than cavitation‐vulnerable oaks under summer dry conditions. Issue 5 (25th August 2021) - Northup, Alison P.; Keitt, Timothy H.; Farrior, Caroline E.
Abstract: Ashe juniper ( Juniperus ashei Buchholz) and escarpment live oak ( Quercus fusiformis Small) are two of the most common woody species of the Edwards Plateau, an arid‐to‐semi‐arid region of nearly 100, 000 km 2 in central Texas. They have very different hydraulic strategies, yet they experienced similar mortality rates during an extreme drought in 2011. We measured J. ashei and Q. fusiformis sap flow velocities during summer dry periods of 2016 and 2017 at six micro‐sites. Although these were years with more‐or‐less average summer conditions, both included significant dry periods. To estimate the relative rate of decrease in sap velocity for each species during the dry periods, we fit a Bayesian exponential decay model to the sap velocity time series for each tree. We found that Q. fusiformis trees were better able to maintain transpiration than J. ashei during dry periods at five micro‐sites and were comparable at the sixth micro‐site. We conclude that it is likely that Q. fusiformis can better maintain transpiration during dry periods than J. ashei, on average, and that in the case of these two species, greater cavitation resistance may not translate to greater drought resistance.